Affine Toda model coupled to matter and the string tension in 2D QCD - Blas, Harold [UNESP] (American Physical Society (APS), 2002)
The (Formula presented) affine Toda model coupled to matter is shown to describe various features, such as the spectrum and string tension, of the low-energy effective Lagrangian of two-dimensional QCD (one flavor and N colors). The corresponding string tension is computed when the dynamical quarks are in the fundamental representation of (Formula presented) and in the adjoint representation of (Formula presented) © 2002 The American Physical Society.